A comparison of muscle damage, soreness, morphology, T2 changes and running performance following an ultramarathon race - Van Niekerk, Wanda (Department of Health and Rehabilitation Sciences, 2016)
Background: Exercise induced muscle damage collectively describes the response to strenuous or unaccustomed exercise. It is well - established that endurance running causes muscle damage. Indirect indicators of muscle damage include the loss of muscle strength, increased levels of muscle proteins, such as creatine kinase, in the blood and delayed onset of muscle soreness. Magnetic resonance imaging has been used to gain insight in to the underlying mechanisms associated with exercise induced muscle damage. The most common approach has focused on changes in transverse (T2) relaxation times after exercise. Given that inflammation and oedema are proposed as reasons for the changes in T2 times, there may be changes in morphological measurements such as muscle volume and peak cross sectional area. Few studies have utilised MRI morphological measurements to assess the effects of exercise induced muscle damage, and there is a lack of evidence regarding changes in muscle morphology after endurance running. Aim: The aim of this study was to investigate changes in transverse (T2) relaxation times and muscle morphology in endurance runners after a 90 km ultramarathon race. Specific objectives: (a) To determine the time course of recovery of muscle pain and plasma creatine kinase activity after a 90km ultramarathon race; (b) to determine changes in 5km time trial performance in an experimental group of endurance runners that took part in a 90 km ultramarathon race compared to a control group of endurance runners that did not take part in a 90 km ultramarathon race; (c) to compare changes in muscle morphology (volume and average cross sectional area) and T2 relaxation times of the quadriceps and hamstrings in an experimental group of endurance runners that took part in a 90 km ultramarathon race and a control group of endurance runners that did not take part in a 90 km ultramarathon race; and (d) to evaluate potential relationships between indicators of muscle damage (plasma creatine kinase levels and muscle pain measurements), morphological muscle changes, and T2 relaxation times in an experimental group of endurance runners that took part in a 90 km ultramarathon race and a control group of endurance runners that did not take part in a 90 km ultramarathon race. Methods: This was a descriptive, correlational study that involved secondary analysis of previously collected data. No new participants were recruited for the study. Participants were allocated to groups, based on whether they took part in a 90 km ultramarathon. The experimental group (n = 11) completed a 90 km ultramarathon. The control group (n = 11) consisted of endurance runners, who ran a minimum of 60 km.wk-1, but did not take part in the ultramarathon. Magnetic resonance images were taken seven days before and 10 - 15 days after an ultramarathon as part of an earlier study. The magnetic resonance images analysis included the digital segmentation and reconstruction of the rectus femoris, combined quadriceps and combined hamstrings muscle groups. Muscle volume and peak cross sectional area was calculated as well as T2 relaxation times. These measurements were correlated with muscle pain and plasma creatine kinase activity measurements obtained during the initial study. Results: There was a significant difference in hamstrings muscle volume between the experimental and control groups. The experimental group had a significantly lower muscle volume compared to the control group (p = 0.03). There was also a significant positive relationship between the T2 relaxation time and plasma CK activity. (r = 0.74; p = 0.04) Conclusion: Changes in muscle morphology in endurance runners are evident after a 90 km ultramarathon. The significant relationship between T2 relaxation times and plasma creatine kinase activity confirms that T2 relaxation time may be used as a non-invasive direct indicator of exercise induced muscle damage.